Cellulose acetate based sustainable nanostructured membranes for environmental remediation. (November 2022) - Rehman, Ayesha; Jahan, Zaib; Sher, Farooq; Noor, Tayyaba; Khan Niazi, Muhammad Bilal; Akram, Muhammad Aftab; Sher, Emina Karahmet
Abstract: Membrane-based gas separation has a great potential for reducing environmentally hazardous carbon dioxide (CO2 ) gas. The polymeric membranes developed for CO2 capturing have some limitations in their selectivity and permeability. There is a need to overcome these issues and developed such membranes having high-performance CO2 capture with cost-effectiveness. The present study aimed to synthesize mixed matrix membranes (MMMs) having improved properties CO2 adsorption performance and stability than that of pure polymer. Further, the effect on CO2 adsorption by increasing the filler concentration in MMMs was investigated. The MMMs were synthesized by incorporating (1–5 wt%) Cu-MOF-GO composites as filler into cellulose-acetate (CA) polymer matrix by adopting the solution casting method. The performance of MMMs was studied by changing the Cu-MOF-GO composite concentration (1–5 wt%) in the polymer matrix at 45 °C up to 15 bar. Morphological analysis by using SEM confirms that by increasing the concentration of Cu-MOF-GO more than 3% will result in their agglomeration in MMM. The successful incorporation of MOF within the polymer matrix of MMMs was confirmed through the presence of functional groups using FTIR and Raman spectroscopy. XRD analysis revealed that pure CA changes its semi-crystalline behaviour into crystalline by the addition of Cu-MOF-GO. The maximum tensile stress and strain rate of MMMs was 45.1 N/mm 2 and 12.8%. In addition, with an increase in (4–5 wt%) Cu-MOF-GO concentration the hydrophilicity of MMMs decreases. The maximum uptake rate of CO2 was 1.79 mmol/g and 7.98 wt% at 15 bar. The adsorption results conclude that Cu-MOF-GO composite and CA-based MMM can be effective for CO2 capture. Graphical abstract: Image 1 Highlights: Cu-MOF-GO filler was incorporated in the CA matrix using the solution casting method. The introduction of Cu-MOF-GO in the CA matrix has improved the morphology of MMM's. Modification has shown remarkable improvement in the crystallinity and stability of MMM's. Enhanced the mechanical properties of Cu-MOF-GO/CA MMM's. The addition of Cu-MOF-GO loading in CA improved the CO2 adsorption uptake capacity.